Estimates of the unreported economy in India - Poonam Gupta; Sanjeev Gupta (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1981)
This paper presents estimates of India's unofficial economy on a yearly basis for the period 1967 to 1978. These estimates implicitly revise the GNP, per capita and other related statistics for this period. The technique employed has been recently used to determine the size of the unreported economies in U.S.A. and Canada. The results indicate that the unreported activity as a proportion of official GNP has grown from 9.5 per cent in 1967 to nearly 49 per cent by 1978. High taxes have contributed significantly to the growth of the unofficial economy. A 1 per cent increase in overall taxes leads to more than 3 per cent increase in the unofficial economy relative to the official economy.
Keywords: 330